4(3+c)+c=9c+4

Simple and best practice solution for 4(3+c)+c=9c+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3+c)+c=9c+4 equation:



4(3+c)+c=9c+4
We move all terms to the left:
4(3+c)+c-(9c+4)=0
We add all the numbers together, and all the variables
4(c+3)+c-(9c+4)=0
We add all the numbers together, and all the variables
c+4(c+3)-(9c+4)=0
We multiply parentheses
c+4c-(9c+4)+12=0
We get rid of parentheses
c+4c-9c-4+12=0
We add all the numbers together, and all the variables
-4c+8=0
We move all terms containing c to the left, all other terms to the right
-4c=-8
c=-8/-4
c=+2

See similar equations:

| (6x−9−2x)=(8+5x−5) | | 6x+-10-4x=-4-11 | | -52=2(-3+4x)+2(3x-2) | | 12/t=6/3 | | (11x+10)+(8x+5)=(4x-5) | | 6.6d=6.4d-3.62 | | 2s+-9=3 | | k-10*9=-k | | 1/3x+131/3=15 | | 1x+12=14-2x | | X2+y2=34X+y=2 | | 3t=2t+13 | | 7f-5=8f+5 | | 36−w=10;w | | 6=x4.5 | | 40x+18x-3=368 | | 2x+49=5x+10 | | 104+t=t | | z+13=3z-13 | | 3x-19=6(x-3) | | 14a=2a-6 | | -5.6c-19.46=12.96+5.28-3c | | -3x=-4.5 | | 38-x=44 | | 36^x=6^x-8 | | 2(-5+m)=-20 | | I=5+i-2*1-2i+3i*i | | Z=5+i-2*1-2i+3i*i | | 36x=6x-8 | | 35=3g-5 | | 16+20m=5m-16+19m | | -x/2+10=12 |

Equations solver categories